Gastrocnemius Activation throughout the Competitive Season in Athletes of Different Experience Levels - Amaro, Catarina M. (2021)
Basketball is a team sport in which the players undergo rapid reactions, and running efforts are usually carried out in all directions. The main goal of the present study was to evaluate the muscle activity response in different basketball movements, considering two types of athletes with different levels of experience. Using a group of nine volunteers, female athletes from a senior basketball team, a data acquisition protocol was defined to identify the changes that occurred throughout the sports season. In this study, to assess the gastrocnemius muscle activity, intensity peak (%MC) and time to peak (TP) were evaluated for five typical basketball skills and movements involving running and jumping with and without the ball. Seven repetitions were executed for each movement, performed at two different time-points of the sports season: at the beginning of the teams’ competition, in November (T1), and at the season peak, in March (T2). TP presents greater values for T2 of the season when compared with T1. The results show that the level of experience of the athletes has a significant effect on the results of TP and %MC, particularly when comparing the two seasons.